Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/su12239916
|View full text |Cite
|
Sign up to set email alerts
|

Self-Sensing Properties of Green Alkali-Activated Binders with Carbon-Based Nanoinclusions

Abstract: This paper is aimed at investigating the self-sensing properties of Portland-free alkali-activated binders doped with carbon-based nanofillers. Four different inclusions (carbon nanotubes, carbon nanofibers, carbon black and graphene nanoplatelets) were added into the matrix in the same amount. The physical and electromechanical properties were analyzed. The self-sensing capabilities of the samples were tested by applying a square wave voltage signal and measuring the variation of electrical resistance during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The polarization of the matrices is a critical issue that requires special attention in WIM sensing applications [37]. Other non-cementitious matrices have been proposed in the literature, including, unsaturated polyester resin [38], epoxy [39], green alkali-activated binders [40] and asphalt concrete with carbon inclusions capable of strain sensing [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…The polarization of the matrices is a critical issue that requires special attention in WIM sensing applications [37]. Other non-cementitious matrices have been proposed in the literature, including, unsaturated polyester resin [38], epoxy [39], green alkali-activated binders [40] and asphalt concrete with carbon inclusions capable of strain sensing [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…To meet the need for increasingly safe and complex structures, contemporary applications demand not only strong and tough, but also multifunctional and smart cement-based material systems, with sensing capabilities and good combination of mechanical, electrical and thermal properties [ 10 , 11 , 12 ]. Smart cementitious materials with enhanced electromechanical properties can help the development of buildings and infrastructures with integrated sensing and health-monitoring capabilities, thus increasing both the structural safety and service life of reinforced concrete structures [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of the mechanical, electrical and thermal performance of mortars with CNT and GNP reinforcements has been the focus of several studies in the literature [ 13 , 14 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Mortar permeability was found to depend on the nano-inclusions due to the increase in absorbed ion chlorides with nanotube loading [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of mechanical properties, the addition of 2D nanomaterials at a certain dosage can significantly increase the strength of the AASC [ 10 ]. Matalkah et al [ 11 ] reported that the addition of 0.2 vol.% Gr nanosheets can improve the compressive strength of AASC by around 15%.…”
Section: Introductionmentioning
confidence: 99%